Analysis Of Factors Of Understanding, Public Awareness, And Tax Sanctions That Affect Public Compliance In Paying Taxes In Persons In The Situgede Area, Bogor - Pramesti, Yulia; Rumiasih, N.A; Rizqi, Muhammad Nur; Yudiana, Yudiana (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
The purpose of this study was to determine the influence of understanding factors, taxpayer awareness, and tax sanctions that can affect taxpayer compliance in paying individual taxes in Situgede Village, Bogor. This research was conducted by taking the object of individual taxpayers in Rw 07 Situgede Bogor Village. Based on the data I obtained, this research was motivated by the reason that there are still many taxpayers who still do not understand and comply with the understanding, awareness of taxpayers, and sanctions in paying taxes. The type of data used in this study is quantitative data with primary data sources derived from questionnaires distributed to respondents through question media. The number of samples distributed in the study were 115 questionnaires but which were returned and processed as many as 111 questionnaires using the sampling method, namely the purposive sampling method. This study uses a descriptive and inferential methodology consisting of (validity test, reliability, descriptive analysis test, classical assumption test, and hypothesis influence test) using a computer application of Statistical Package for the Social Sciences (SPSS) version 25, while the results of the data processing are there is a positive and significant effect of understanding, taxpayer awareness, and tax sanctions on individual taxpayer compliance.